Aeroelastic analysis of 10 MW wind turbine using CFD–CSD explicit FSI-coupling approach. (May 2019) - Sayed, M.; Lutz, Th.; Krämer, E.; Shayegan, Sh.; Wüchner, R.
Abstract: The aeroelastic response of the generic DTU 10 MW horizontal-axis wind turbine blades is investigated employing a time-accurate CFD–CSD loose coupling approach. An FSI coupling approach is implemented and used to conduct the aeroelastic simulations. The block-structured CFD solver FLOWer is employed to obtain the aerodynamic blade loads based on the time-accurate solution of the URANS equations. The CSD solver Carat++ is utilized to calculate the elastic deformations based on non-linear Timoshenko beam elements. Due to the rotor elasticity, the wind turbine power and thrust are increased by approximately 1% and 0.3% respectively. That increase is due to the large edgewise deformations which make the radial force component contribute to the rotor torque. Due to the presence of the tower in the coupled simulations, the forces and the deformations are reduced while the blades are crossing the tower. A time delay in the structural response due to the forces reduction causes a phase shift of 30°between the deformations reduction and the forces reduction. Also, the 1P amplitude of the wind turbine is reduced due to the blade flexibility by 6%, 12% and 22% at r ∕ R = 0 . 3, 0.6 and 0.9 respectively.